On the Use of Historical Bathymetric Data to Determine Changes in Bathymetry: An Analysis of Errors and Application to Great Bay Estuary, NH - Jakobsson, Martin; Armstrong, Andrew; Calder, Brian; Huff, Lloyd; Mayer, Larry; Ward, Larry (The International Hydrographic Review, 2005)
The depth measurements that are incorporated into bathymetric charts have associated errors with magnitudes depending on the survey circumstances and applied techniques. For this reason, combining and comparing depth measurements collected over many years with different techniques and standards is a difficult task which must be done with great caution. In this study we have developed an approach for comparing historical bathymetric surveys. Our methodology uses Monte Carlo modelling to account for the random error components inherited in the data due to positioning and depth measurement uncertainties.